Cholinesterase Inhibitor Use in Patients With Dementia Admitted to a Palliative Care Unit. (November 2021) - Perri, Giulia-Anna; Wilson, Jessica; Gardner, Sandra; Berall, Anna; Kirstein, Anne; Khosravani, Houman
Objectives: Current guidelines suggest that patients with severe dementia on cholinesterase inhibitors (CHEIs) should discontinue their CHEIs by taper. This study aims to define the prevalence of patients admitted to a palliative care unit (PCU) with dementia on a CHEI and to determine whether these patients were tapered off their CHEIs according to current deprescribing guidelines. Design: This is a descriptive retrospective chart review that examined patients admitted to a PCU with dementia on a CHEI from January 2015 to June 2019. Methods: Individuals admitted to the PCU with a primary or comorbid diagnosis of dementia were identified. Their corresponding CHEI dose, frequency and discontinuation pattern were identified. Data were analyzed using descriptive statistics. Results: A total of 36 patients were admitted to the PCU with dementia on a CHEI (prevalence of 2.3%). The median length of stay was 21 days. For 31 of these patients, their CHEI was discontinued, only 9 of which had a taper. Of the 24 patients who discontinued their CHEI suddenly, 10 patients had an order to discontinue their CHEI in the last 2 days before their date of death. Conclusion: This study suggests that although patients admitted to a PCU with dementia have their CHEI discontinued, the discontinuation was done without a taper. In many cases the CHEIs were continued through the active stage of dying. Future work should explore reasons why PCU physicians are mostly late to taper CHEIs for patients admitted with dementia.